Economic viability and environmental impact investigation for the biofuel supply chain using co-fermentation technology. (1st February 2020) - Li, Yu; Kesharwani, Rajkamal; Sun, Zeyi; Qin, Ruwen; Dagli, Cihan; Zhang, Meng; Wang, Donghai
Highlights: An optimization model of co-fermentation biofuel supply chain is proposed. The performance of co-fermentation based biofuel supply chain is investigated. Both economic and environmental performance measures are examined. A case study based on Missouri in U.S. is implemented. Various stover harvesting rates are examined. Abstract: Co-fermentation of cellulosic biomass and grain to produce bioethanol has been proposed to integrate first- and second-generation biofuel production technologies. This method can relieve the food versus fuel competition due to the use of edible matter of crop in first-generation biofuel production. It can also boost the low ethanol concentration and thus reduce the unit production cost when using cellulosic biomass as well as green the energy footprints when preprocessing cellulosic biomass in second-generation biofuel production. In this paper, we examine the economic performance and environmental footprint of the biofuel supply chain using co-fermentation production technology. The cost and greenhouse gas emissions per unit bioethanol produced are quantified and compared to the performances of first- and second-generation biofuel production technologies. The mathematical models for the biofuel supply chain using three different biomass types are proposed. A numerical case study based on the State of Missouri in the United States is implemented. The results of the case study show that a co-fermentation based supply chain can effectively address the concern of food versus fuel competition of corn sourced supply chain and the issues of low sugar yield, high energy footprints, and high unit cost of corn stover sourced supply chain.